A placental mammal-specific microRNA cluster acts as a natural brake for sociability in mice - Lackinger, Martin; Sungur, A. Özge; Dieterich, Christoph; Schwarting, Rainer; Wöhr, Markus; Schratt, Gerhard (EMBO reports, 2019)
Aberrant synaptic function is thought to underlie social deficits in neurodevelopmental disorders such as autism and schizophrenia. Although microRNAs have been shown to regulate synapse development and plasticity, their potential involvement in the control of social behaviour in mammals remains unexplored. Here, we show that deletion of the placental mammal-specific miR379-410 cluster in mice leads to hypersocial behaviour, which is accompanied by increased excitatory synaptic transmission, and exaggerated expression of ionotropic glutamate receptor complexes in the hippocampus. Bioinformatic analyses further allowed us to identify five ?hub? microRNAs whose deletion accounts largely for the upregulation of excitatory synaptic genes observed, including Cnih2, Dlgap3, Prr7 and Src. Thus, the miR379-410 cluster acts a natural brake for sociability, and interfering with specific members of this cluster could represent a therapeutic strategy for the treatment of social deficits in neurodevelopmental disorders.